Impact of the changes in neurohumoral factors on the formation of violations of the diastolic filling of the left ventricle in adolescents with myocardial pathology - L.F. Bohmat; V.V. Nikonova (Zaslavsky O.Yu., 2017)
The purpose of the study was to investigate the state of neurohumoral regulation in various nosological forms of myocardial pathology depending on the type of diastolic dysfunction (DD). Materials and methods. A comprehensive survey was performed in 110 adolescents aged 13-18 years with myocardial pathology, including 40 - with cardiac arrhythmias, 40 - with dysplastic cardiomyopathy and 30 - with primary hypertension. The control group consisted of 10 apparently healthy peers with no signs of heart disease. Morphofunctional cardiac parameters were studied using ultrasound in M and B modes by the standard method. Diastolic function of the left ventricle was studied in pulsed Doppler mode with registration transmitral flow from the apical access of the four-chamber heart. Assessment of the functional status of sympathoadrenal system was carried out by the content of free catecholamines in daily urine - adrenaline and noradrenaline using fluorometric method according to E.Sh. Matlina et al. (1976). Studying renin-angiotensin-aldosterone system (RAAS) included investigation of plasma renin activity, content of angiotensin II and aldosterone in peripheral venous blood using radioimmunoassay analysis, which was performed on gamma counter Narcotest. We have used sets "Angiotensin-1-renin", "Angiotensin II", "Aldosterone" manufactured by Immunotech (Czech Republic). Statistical analysis of the material was held on the IBM PC/Pentium 4 using application package Statgraphics Centurion. Results. As a result of the studies in boys with cardiac arrhythmias, there was found a probable sympathoadrenal system activation in groups with both the first (I), and the third (III) types of DD. Indicators of sympathoadrenal system in the group with DD type II almost did not differ from control values. Exploring the state of the RAAS in patients with cardiac arrhythmias, it was found the gradual activation of plasma renin from the group with DD type I to the group with type III. A similar trend was observed regarding angiotensin II, but the difference was not significant. Aldosterone indicators almost did not differ from control values. Adolescents with dysplastic cardiomyopathy in the group with type I DD of the left ventricle had significantly higher parameters of sympathoadrenal system, both adrenaline (p < 0.01) and noradrenaline (p < 0.05), while in groups of DD types II and III, these figures did not differ from control values. When assessing the parameters of RAAS, a gradual increase in renin activity of the blood plasma from group I to group III (p < 0.01, p < 0.01, p < 0.01, respectively) attracted attention, angiotensin II values also increased, but the difference between groups with different types of DD was not significant. The value of aldosterone did not differ much from the control group, regardless of the DD type. In the group of adolescents with primary hypertension, we have found a significant increase in urinary catecholamines, regardless of DD. Changes in RAAS values were mixed. Thus, plasma renin activity was higher in adolescents with DD type II (p < 0.05) and III (p < 0.01), the level of angiotensin II prevailed in the group with DD type I (p < 0.05), while aldosterone levels - with DD type III (p < 0.01). Conclusions. The development of diastolic dysfunction in adolescents with myocardial pathology occurs against the background of neurohormonal system activation. People with type I diastolic dysfunction, regardless of myocardial pathology, are characterized by a significant activation of sympathoadrenal system. In adolescents with types II and III of diastolic dysfunction, there is a consistent involvement of the renin-angiotensin-aldosterone system in the pathological process, especially in adolescents with hypertension.